RANCANG BANGUN SISTEM KONTROL DAN MONITORING PH, SUHU AIR DAN TDS PADA SISTEM AKUAPONIK BERBASIS INTERNET OF THINGS (IOT) - Ubaidillah Umar (P3M Politeknik Negeri Indramayu, 2024)
As time goes by, agricultural land in urban areas has decreased. Aquaponics can be an option for agricultural development in urban areas. However, in the field, there are obstacles where the condition of the fishpond water is uncertain in providing nutrients for the plants. To respond to this condition, this research developed a system by implementing an IoT system that is integrated with a rule-based control system to control and monitor nutritional quality by the needs of aquaponic-based plants. This technology includes controlling pH levels, water temperature, and TDS (total dissolved solids) produced by fish waste in the aquaponic system to be used as nutrition for plants. This system requires several sensors and main components, including a ph meter sensor, TDS, and temperature sensor, which are integrated and processed via the ESP32 microcontroller. The system measurement results are controlled and sent to the IoT Cloud database connected by an internet connection. This IoT-based aquaponics system can be monitored in real-time. The test results on the system show that the sensors used have a small reading error, namely the temperature sensor showing an error value of 1.5%, the PH sensor 0.7%, and the TDS sensor 0.9%. In this way, the level of accuracy when using sensors can be guaranteed. The research results show that the control and monitoring system design works according to needs, where the system that is controlled and integrated with the website system can run with a 100% success rate, which can facilitate the care and maintenance of plants and fish by farmers.